The Effect of the Thickness of Fine Grain Sized Material, Grain Cliameter and Slope on Carrying Capacity - Yildiz, Servet; Kelestemur, Oguzhan (Gazi Univ, 2005)
In this study, the effect of the thickness of fine grain sized material taken from Elazig province used in the earth fills on carrying capacity was investigated. Fine grain sized material which was repbeed as 5, 10, 15 and 20 cm of thickness and squared was laid down in to the experimental set up. The filling materials having 4.76, 9.53, 19.5, 24.40 and 40.00 mm of radii and 1/4, 1/3.5, 1/3, 1/2.5 and 1/2 of slopes were laid down of them. The filling materials were subjected to loading until the failure of material. The same filling materials have been prepared at the optimum water rate and tested for carrying capacity. From experimental results, it is seen that the carrying capacity decreases with increasing the thickness of fine grain sized materials and it increases with increasing the grain size and the slope of the filling material. In addition, the carrying capacity considerably decreases with the filling materials prepared at the optimum water rate. As a matter of feet, the carrying capacity, the thickness the radius and the slope of the filling material were studied and the nedationships were pusented in various graphs.
Keywords: Slope; fill; fine grained material; carrying capacity; grain size